Parameter identification of soil-pile system by the dynamic testing method - Khiem, Nguyen Tien (Vietnam Journal of Mechanics, 1997)
This paper deals with a problem to determinate parameters of soil and pile by measurements of natural frequencies and damping ratios of the system. There was suggested a model of soil-pile system, which includes more unknown parameters of soil to be determined. Here is given also mathematical base for extraction of modal parameters from measured spectral characteristics. The most important result obtained in this study is a procedure and' program carried out to determinate the pile length (L), elastic coefficients of soil around pile and at the bottom end of pile and also the damping coefficient of soil. Numerical test by the program shows high accuracy and validates effectiveness of the procedure.